2017
DOI: 10.5606/kbbihtisas.2017.09623
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between septal deviation and concha bullosa

Abstract: Objectives: This study aims to classify septal deviations according to the Mladina classification and to investigate the relationship between concha bullosa and septal deviation. Patients and Methods:A total of 407 patients (229 males, 178 females; mean age 30.9±13.3 years; range 14 to 69 years) who admitted to our clinic with nasal obstruction, were identified to have deviation, and detected to have concha bullosa on computed tomography were included in the study. Patients' age, gender, type of deviation acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Moorthy et al demonstrated that an S-shaped NSD was significantly correlated with sinus diseases, including cases where nasal symptoms were absent 20. Erkan et al21 suggested that both NSD and CB might affect each other physically. In the literature, few studies were found that sought to assess the correlation between NSD and the presence of middle turbinate pneumatization; however, a study demonstrated a highly significant correlation between the presence of middle CB and a deviated septum on the contralateral side 18.…”
Section: Discussionmentioning
confidence: 99%
“…Moorthy et al demonstrated that an S-shaped NSD was significantly correlated with sinus diseases, including cases where nasal symptoms were absent 20. Erkan et al21 suggested that both NSD and CB might affect each other physically. In the literature, few studies were found that sought to assess the correlation between NSD and the presence of middle turbinate pneumatization; however, a study demonstrated a highly significant correlation between the presence of middle CB and a deviated septum on the contralateral side 18.…”
Section: Discussionmentioning
confidence: 99%
“…Biconvex NSD and contralateral inferior concha hypertrophy can lead to bilateral nasal obstruction in patients with NSD.However, contralateral CB could also be the cause of this symptom. Keles A study conducted by Erkan et al [23] suggested that both NSD and CB might affect each other physically. Few studies in literature were found that sought to assess the correlation between NSD and the presence of middle turbinate pneumatization; however, a study by Kapusuz Gence et al demonstrated a highly significant correlation between the presence of middle CB and a deviated septum on the contralateral side.…”
Section: Cases Respectivelymentioning
confidence: 99%
“…In clinical settings, concha bullosa is often asymptomatic in its early stages, and is commonly discovered during other medical procedures. It can become clinically significant if the conchal enlargement narrows the nasal meatus obstructing nasal flow (Erkan et al 2017). Concha bullosa may require surgical intervention to remove or reduce the affected concha or conchae.…”
Section: Introductionmentioning
confidence: 99%